Achieving sustainable development goals in the context of socially oriented government programs and national projects - Sheina, Ekaterina; Kochieva, Janna (E3S web of conferences, 2023)
Achieving sustainable development goals is a strategic guideline for the national economies of most countries, which is embodied through the establishment of socially oriented investment and stimulating the involvement of socially oriented stakeholders in the investment process, the most important of which is the state. At the state level, socially oriented investment projects are various state programs and national projects implemented with the help of a wide range of entities in interaction with the state - development institutions, business communities, private investors. The motivation for participation in these programs and projects is the presence of specialization as a key characteristic of investors with a social orientation of investment goals, which is reflected in the scientific and theoretical approach proposed by the authors in this study and built on the relationship between the level of specialization, the percentage of budget funds spent, and the assessment of the organization of synchronicity interaction between stakeholders of the investment process, as well as the formation of the goals of socially oriented investment.